QUR’AN RECITATION IN KENDURI DOA SELAMAT AT SANDAKAN, SABAH, MALAYSIA (At-Tibyan, 2023)
This study discusses the recitation of the Quran in a kenduri doa selamat at Sandakan, Sabah, Malaysia. This research aims to find out how the kenduri doa selamat is performed, the verses of the Qur’an used as well as the community’s understanding toward the verses used in the kenduri doa selamat at Sandakan, Sabah, Malaysia. The research approach that the author used is the living Qur'an to find the meaning and the purpose of reciting the verses of the Qur'an in the kenduri doa selamat among the society in Sandakan, Sabah, Malaysia. Findings of this study found that the purpose of the thanksgiving ceremony or known as 'Kenduri Doa Selamat' is to be express gratitude for the favors that have been bestowed, pray for safety and also increase the practice of almsgiving. This act Kenduri Doa Selamat is performed by the local Muslim priest or Imam whereby the residents who participate  recite the verses of the Qur'an and the prayers together. This activity has become a habit of the local community and is also a positive thing to implement to liven up the recitation of the Qur'an in public.